Penerapan Value Stream Mapping untuk Allocation Planning di PT. X - Widjaja, Felicia Tedja; Halim, Siana (Jurnal Titra, 2015)
PT. X is one of the cigarette manufacturing leaders in Indonesia. Products from PT. X is distributed inside and outside Indonesia through a number of markets. Therefore, a good Allocation Planning is a must. PT. X wants to map the activities in the Allocation Planning and Value Stream Mapping (VSM) is chosen for accomplishing that task. First, we map the current situation using VSM, we found two wastes occurred during the Allocation Planning, which are waiting time and motion. After that, various improvements are executed to reduce those wastes, and then once more the VSM are applied. The results showed that in overall the lead time decrease over 34.88%.